Tales of rationality: the rational emotive behavioral monomyth as a metaphorical alignment of rational emotive behavior therapy and the Hero’s Journey narrative structure - Martin J. Turner (Frontiers in Psychology)
In the present paper, a metaphor is proposed for the depiction of rational emotive behavior therapy (REBT) with a view to aiding practitioner and client comprehension of the fundamental processes of REBT. Specifically, it is argued that the processes, and broad framework, of REBT is akin to an archetypal narrative story structure known as the Hero’s Journey, or monomyth. In the Hero’s Journey, an ordered narrative framework is followed that presents the heroic story of a protagonist, a device that has been employed across art, literature, film, and marketing. In the present paper, this Hero’s Journey story arc is used as a metaphor for REBT, with each stage of the Hero’s Journey related to a part of REBT theory and application. In the current paper, the alignment of the components of the Hero’s Journey and the components of REBT are presented in some detail. The author describes this approach as the rational emotive behavioral monomyth (REBM) and outlines how it can be positioned and applied in practice.